Strategic Marketing Management: Unveiling Consumer Psychology through Qualitative Analysis and Literature Review - B. Bungatang; Edy Jumady; Firman Ali; Ramlan Natsir (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
The purpose of this qualitative research study is to explore consumer psychology and its implications for strategic marketing management. Grounded in the grounded theory methodology, the study aims to delve into the multifaceted nature of consumer decision-making processes, the influence of emotions on brand perception, the role of social media in shaping consumer behavior, and the significance of brand identity and differentiation in the competitive marketplace. The research methodology involves a comprehensive review of existing literature related to consumer psychology and strategic marketing management, encompassing scholarly articles, books, and reports. Data analysis procedures include systematic coding, categorization, and interpretation of qualitative data extracted from the literature. The key findings of the study underscore the intricate interplay of factors influencing consumer behavior, including attitudes, emotions, social norms, and perceived behavioral control. Emotions emerge as a crucial determinant of brand perception, with positive emotional experiences fostering brand loyalty and negative emotions undermining consumer trust. Social media platforms play a pivotal role in shaping brand perceptions and purchase decisions, while brand identity serves as a strategic asset for differentiation and market positioning. The study contributes to a deeper understanding of consumer psychology and provides insights for marketers to develop targeted and effective marketing strategies that resonate with consumers' motivations and preferences.